1 William Waller Hening, The Statutes at Large: Being a Collection of all the Laws of Virginia 127 (1809) - (:unkn) unknown (My University, 1624)
"That men go not to worke in the ground without their arms (and a centinell upon them)." And "That the commander of every plantation take care that there be sufficient of powder and amunition within the plantation under his command and their pieces fixt and their arms compleate."
Keywords: REQUIRED POSSESSION